Integration of balanced scorecard and analytical hierarchy process to measure the performance of supporting unit in aircraft maintenance service companies - Utami, Nur Aulia; Dewayana, Triwulandari; Septiani, Winnie (Operations Excellence: Journal of Applied Industrial Engineering, 2024)
Dynamic and challenging business environment in the aircraft maintenance services industry require company to survive and ensure business continuity. To realize effective performance, performance measurement is needed as a management system for managing and controlling performance. The purpose of this research is to measure the performance of supporting unit at PT. XYZ by using balanced scorecard framework that is integrated with AHP. The steps in this research includes identification strategy objective, identification key performance indicator (KPI), design and measure performance using integrated balanced scorecard  and AHP. The method used in this study combines quantitative data with the Analytical Hierarchy Process (AHP) approach. The AHP method is used for KPI weighting. The design of KPI weights for each perspective in balanced scorecard are 42,3 % for the learning and growth, 33,5% for internal business process, 17,3% for financial, and 6,8% for the customer perspective.  The results of supporting unit performance show the lowest score in the learning and growth perspective with average performance indicator, while in internal business process, financial and customer perspective have good performance indicator. The result of measuring total performance of four perspective are 74,5% which indicates that the performance of PT.XYZ’s BSC is in the good enough category.